2012
DOI: 10.1021/ma3014806
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Spin Capturing Polymerization of Ethylene

Abstract: International audienceEnhanced spin capturing polymerization (ESCP)-a recent and versatile technique in the field of controlled radical polymerization-achieves control over molecular weights and the synthesis of complex copolymer structures for a wide range of monomers. In the present work, the use of ESCP was extended to the radical polymerization of ethylene under mild conditions (low temperature and medium ethylene pressure) using a nitrone as spin trapping agent. It was demonstrated that the evolution of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Xanthate proved to be extremely efficient to control the polymerization in these cases (the process is also called macromolecular design by interchange of xanthates, MADIX) 17. Considering ethylene as a non‐activated monomer, we took advantage of our recent progress in efficiently performing the free‐radical polymerization of ethylene under mild conditions ( T <100 °C, P <300 bars)1820 to investigate the RAFT polymerization of ethylene mediated by xanthates. To the best of our knowledge, this has never been done before.…”
Section: Methodsmentioning
confidence: 99%
“…Xanthate proved to be extremely efficient to control the polymerization in these cases (the process is also called macromolecular design by interchange of xanthates, MADIX) 17. Considering ethylene as a non‐activated monomer, we took advantage of our recent progress in efficiently performing the free‐radical polymerization of ethylene under mild conditions ( T <100 °C, P <300 bars)1820 to investigate the RAFT polymerization of ethylene mediated by xanthates. To the best of our knowledge, this has never been done before.…”
Section: Methodsmentioning
confidence: 99%
“…Xanthate proved to be extremely efficient to control the polymerization in these cases (the process is also called macromolecular design by interchange of xanthates, MADIX). [17] Considering ethylene as a non-activated monomer, we took advantage of our recent progress in efficiently performing the free-radical polymerization of ethylene under mild conditions (T < 100 8C, P < 300 bars) [18][19][20] to investigate the RAFT polymerization of ethylene mediated by xanthates. To the best of our knowledge, this has never been done before.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies on the free-radical polymerization of ethylene, [18][19][20] we demonstrated that it was crucial to use dimethylcarbonate (DMC) as solvent in order to minimize irreversible chain-transfer reactions and to guarantee high productivity. RAFT polymerizations were thus performed in dichloromethane (DMC) at 200 bars and 70 8C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Segmented copolymers, containing blocks of propylene or ethylene as well as functionalized polyolefins are topic of intense research and development, however, their analytical characterization is troublesome. The breakthrough in liquid chromatography of polyolefins, which came with the application of PGC as stationary phase, has enabled recently the realization of LCCC for linear PE at high temperature (160 °C) by Mekap et al Yet, LCCC of PP has been unknown.…”
Section: Introductionmentioning
confidence: 99%